RESEARCH BEHAVIOUR, INTELLECT AND CREATIVITY OF FUTURE DOCTORS OF PHILOSOPHY IN THE PROCESS OF ACQUIRING FOREIGN LANGUAGE COMMUNICATIVE COMPETENCE: PSYCHOLOGICAL PERSPECTIVE (Psychology Travelogs, 2025)
The article analyses the psychological aspects of the relationship between research behaviour, intellect and creativity of future doctors of philosophy in the process of acquiring foreign language communication skills. Despite the obviousness that there must be a positive correlation between research behaviour, intelligence and creativity, it is far from always being found in empirical studies, and in some cases negative correlations are observed.It considers studies in which the links between research behaviour, intellect and creativity were examined at the level of correlations between the corresponding tests. In turn, research has been conducted on the interrelationships and interactions between research behaviour, intelligence and creativity that arise or are actualised in the holistic act of learning new objects while studying and using a foreign language. Some of the diverse results obtained are starting points for new directions in the cognition of the object, which are realised through the setting of new goals, the search for and identification of new courses of action and testing strategies, and the construction of new systems of interpretation taking into account the foreign language being studied. Thus, divergent thinking is stimulated by new information coming from the object as a result of the application of divergent strategies. It is particularly important that a person's creative focus on the diversity of all components of activity is the basis for the invention of various combinatorial strategies, a complete combinatorial search of several factors, understanding a special type of information revealed by these combined influences (information about unobservable interactions between factors), and constructing an adequate system for interpreting the object's operation.
Keywords: research behaviour; intelligence; creativity; tests; divergent thinking; foreign language learning; foreign language communicative competence